Respon Pertumbuhan dan Hasil Tanaman Cabai terhadap Aplikasi Fungi Mikoriza Arbuskular (FMA) Berbagai Media Pasir (Jurnal Agro Teknologi Tropika, 2014)
Chili production in Indonesia is less than optimal due to many factors, such as plant disease and pest attack. Plantdisease and pest attack can be controlled with increased resistance of plants through plant breeding, genetic engineering,as well as by inducing plant resistance using microbes such as Arbuscular Mycorrhizae Fungi (AMF). This researchaims to study the effect of the potential of the growth and resistance of chili crops, AMF exploration needs to be doneand propagated in two types of medium sand to facilitate application in chili. Stages of research are the exploration,identification and propagation of AMF and test preparation of chili crops. AMF inoculum propagation results withsand mediums are used in research as much as 50 g, 100 g, 150 g and 200 g per polybag. AMF inoculum was added tothe planting hole with time transplanting. This research used a completely randomized design with three replications.The purpose of this study was to determine the response of the growth and yield of chili crops on the application of FMAin sand medium. Variables measured include crop height, number of leaves, number of flowers, number of fruits, fruitweight and percentage of fruit maturity. Based on the results of this study concluded that the multiplication of AMFspores in the medium sand gives good results. The number of spores on the mountain sand is higher than the sea sand. Allvariables of growth and yield of chili crops treated with AMF showed good results and significantly different than thecontrol. The author recommends to use a formulation FMA medium sand mountain with 200g dose because it producesthe highest fruit weight .Keywords : Arbuskular Mycorrhiza Fungi, sand medium, chilli crops.